ANTIBACTERIAL ACTIVITY TEST OF PINEAPPLE JUICE (Ananas comosus L.) AGAINST THE GROWTH OF Escherichia coli: UJI AKTIVITAS ANTIBAKTERI SARI NANAS (Ananas comosus L.) TERHADAP PERTUMBUHAN Escherichia coli - Resmila Dewi; Cut Suraiya Wahyuni Utami; Erda Marniza; Widya Angreni; Rina Kurniaty (PT. ROCE WISDOM ACEH, 2026)
Pineapple (Ananas comosus L.) is known to contain active compounds that have antibacterial potential. This study aims to evaluate the antibacterial activity of pineapple juice and determine the effective concentration required to inhibit the growth of Escherichia coli. The antibacterial activity test was conducted using the disc diffusion method at three concentrations (20%, 25%, and 30%), with chloramphenicol as the positive control and distilled water as the negative control. The antibacterial activity test showed that pineapple juice at 20%, 25%, and 30% produced inhibition zones against Escherichia coli of 13.83 mm, 16.33 mm, and 18.50 mm, respectively. Based on the study results, pineapple juice shows antibacterial activity against Escherichia coli, with the most effective concentration for inhibiting bacterial growth at 30%.